Assessment Widal Test for leukocyte Counting for Diagnosis of Salmonella typhi in Nineveh - Muhsen Essa; Bushra Hamed (College of Education for Pure Sciences, 2008)
Abstract This study was conducted for evaluating laboratory diagnosis reality of Salmonella typhi which causes typhoid fever that is considered one of an important health problems in Iraq. Questionnaire study showed, that physicians depend on both of laboratory results and clinical symptoms in order to diagnose typhoid fever (83.6) % and there is an limited dependence on clinical symptoms only (13.7) % or laboratory results only (2.7)% . There are a high rate of these physicians (78)%stated that there were insufficient accuracy about Widal test which is considered the unique laboratory test used by laboratories, also, results showed that Widal test represents (95.6)% of laboratory methods which is used to diagnose Salmonella typhi and culturing methods is limited (4.4)% or not existed . When Widal test results were evaluated which is done in different health analysing laboratories in Nenavah province by using Widal test (dilution method) the results showed great differences of results whether result type (positive or negative) or kind of antigens which showed positive results. When leukocyte count was used as a test to support the diagnosis of typhoid fever, it was shown that there is a relation between typhoid fever and decreasing leukocyte count in these patients.